From bench to bedside: Seeing the future of ischaemic post-conditioning as a novel cardioprotective therapy - von Klemperer, Alex (SA Heart Journal, 2017)
In order to improve the survival of patients suffering from an acute myocardial infarction, it is crucial to limit the size of the infarct. In the laboratory, several promising treatment strategies have been developed, but very few of these have been successfully translated from bench to bedside. This review aims to evaluate the translation of a novel therapy, ischaemic post-conditioning that can reduce infarct size and salvage myocardial function after acute myocardial ischaemia, from bench to bedside. The phenomenon of post-conditioning refers to staccato bouts of ischaemia at the onset of reperfusion. By elucidating the signalling mechanisms involved in the post-conditioning process, it has been possible to determine several pharmacological agents that deliver an equivalent level of protection. Following a large number of successful initial laboratory testis, small clinical trials suggest a promising future for this therapy. However, the breakthroughs required for this effective laboratory phenomenon to translate into meaningful clinical therapies can only be achieved by careful application of data obtained in basic research and controlled trials.